2016
DOI: 10.1186/s12957-016-1031-1
|View full text |Cite
|
Sign up to set email alerts
|

10 % fluorescein sodium vs 1 % isosulfan blue in breast sentinel lymph node biopsy

Abstract: BackgroundSentinel lymph node biopsy (SLNB) is well accepted to be a standard procedure in breast cancer surgery with clinically negative lymph nodes. Isosulfan blue is the first dye approved by the USA Food and Drug Administration for the localization of the lymphatic system. Few alternative tracers have been investigated. In this study, we aimed to compare the differences between 10 % fluorescein sodium and 1 % isosulfan blue in breast sentinel lymph node biopsy and to investigate the feasibility of using 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Since then, there has been considerable progress in the use of such “lymphatic tracers” but, in general, these tracers exhibit light staining, poor diffusion, and nonuniform particles, which can lead to misjudgments by surgeons. 15 , 22 Moreover, the injection time of pigments or lymphatic tracing methods is not easy to control.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, there has been considerable progress in the use of such “lymphatic tracers” but, in general, these tracers exhibit light staining, poor diffusion, and nonuniform particles, which can lead to misjudgments by surgeons. 15 , 22 Moreover, the injection time of pigments or lymphatic tracing methods is not easy to control.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the proteins, radiological tools are expensive, ranging from $280 for HRCT to $807 for MRC ( 6 ). On the other hand, an ampule of 10% fluorescein costs only $1.7 ( 25 ), and is widely available, as it is used in many ophthalmic procedures and brain tumor surgeries ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, several authors also reported the use of fluorescein dye in breast cancer for SLN biopsy detection. [25][26][27][28] Earlier margin assessments methods are described in review article 29 and as per author's knowledge no one has used fluorescein dye in fluorescence spectroscopy for breast cancer margin assessment during surgery before our study.…”
Section: Theoretical Backgroundmentioning
confidence: 99%